Effectiveness Of Direct Cash Assistance Policy Village Funds On Economic Recovery During The Covid-19 Pandemic - Arrahman; Yadi Arodhiskara; Nurwani M (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
Village funds are a mandate from the law as stipulated in article 72 paragraph 2 of Law Number 6 of 2014. As one of the village revenues, the central government is obliged to allocate village funds in the state budget (APBN), in 2022 policies and distribution village funds by taking into account village characteristics and village performance in managing village funds. Meanwhile, the mechanism for channeling village funds for 2022 will remain the same as for 2021. Where, village funds will be transferred directly from the central account to the village account. This study aims to determine the management of direct village fund cash assistance and the effectiveness of village fund cash direct assistance policies in economic recovery during the Covid-19 pandemic in Wanio village. As for the data collection techniques used in this study, namely observation, interviews and documentation. The sample in this study consisted of 9 people, namely 1 village head, 1 financial officer, 1 BPD chairman and 6 members of the community. The data analysis technique in this research is descriptive research. Direct village cash assistance during the pandemic in 2021 based on regulations issued by the Ministry of Village Permendes PDTT No. 7 of 2021 regarding the priority policy on the use of Village Funds has been fully implemented in accordance with existing regulations.